2007
DOI: 10.1111/j.1751-7893.2007.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood negative experiences and subclinical psychosis in adolescence: a longitudinal general population study

Abstract: Background: Accumulating evidence suggests that experiences of trauma and victimization during childhood are associated with an increased risk to develop clinical and subclinical psychosis in adulthood. A recent cross-sectional study showed a significant association between trauma and psychotic experiences in adolescents. The current study aimed to extend these findings by investigating the longitudinal effects of negative life experiences on the risk for subclinical psychotic symptoms 2 years later in an adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 53 publications
(108 reference statements)
2
34
0
Order By: Relevance
“…Given that the development of a psychotic disorder is a relatively rare event, cohort studies have often focused on psychotic symptoms and not on disorder. [12][13][14] When studies have investigated psychotic disorder as an outcome, the number of available cases has been low and the measures used to diagnose psychosis relatively broad. 8,10 The measures of trauma used in these studies have also been relatively crude in the context of large epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the development of a psychotic disorder is a relatively rare event, cohort studies have often focused on psychotic symptoms and not on disorder. [12][13][14] When studies have investigated psychotic disorder as an outcome, the number of available cases has been low and the measures used to diagnose psychosis relatively broad. 8,10 The measures of trauma used in these studies have also been relatively crude in the context of large epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of trauma, one of the most extensively studied risk factors in relation to psychosis (Read et al, 2005), has been associated with later diagnosis of schizophrenia (or other psychotic disorder) (Cutajar et al, 2010;Fisher et al, 2006;Lardinois, et al, 2010) as well as with subclinical psychotic experiences (Arseneault et al, 2011;Lataster et al, 2006;de Loore et al, 2007). The current thesis showed that trauma also is associated with persistence of subclinical psychotic experiences in both adolescents and young adults.…”
Section: Development and Its Contextmentioning
confidence: 70%
“…Furthermore, associations were usually stronger with increasing frequency and severity of the trauma experienced (Arseneault et al, 2011;de Loore et al, 2007;Lataster et al, 2006;Read et al, 2005) and when there was an intention to harm (Arseneault et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization 2 , at any point in time, there are an estimated 450 million people in the world who are afflicted by some sort of mental, neurological, or behavioural problem. These problems often begin in adolescence and persist through to adulthood 3-5 . Similarly, strong connections between emotional health and bullying (whether as a victim or as a bully) have been found across several countries [6][7][8][9][10] . Early adolescence is a particularly vulnerable time for the onset of mental health problems and the occurrence of bullying 11 .…”
Section: Introductionmentioning
confidence: 99%